REJECTION OF DOGMA - Henrikas Zabulis (Problemos)
In the course of the first post-war years, Eugenijus MEŠKAUSKAS lectured on almost all Marxist dis-ciplines, though he was a non-party man. As early as that period, under the conditions of Stalinist dogmatism, he managed to think and behave in a tolerant and farsighted way. Later on, his ability to question everything what was officially accepted in the Marxist theory has formed a gighly original school of the University philosophers, which attracted strong enough criticism of official institutions, but made a great impact on academic youth. Eugenijus MEŠKAUSKAS himself and through his pupils, due to the universal character of the subject he taught and his non-dogmatic thinking, has coloured at least two generations of Lithuanian intellectuals - graduates of Vilnius University. They belonged to the stratum of society where the reformation ideas have rapidly found their rich soil.